Literature Review: Enhancing Awareness of A Healthy Lifestyle Culture Among College Students - Priastuti T, Maya; Suwanti, Suwa; Safitri, Indah (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
The development of modern lifestyles has led many college students to adopt unhealthy habits, resulting in suboptimal awareness of a healthy lifestyle culture. Many factors influence awareness of healthy living. This study aims to examine the factors influencing and strategies for improving awareness of a healthy lifestyle culture among university students. This study employed an analytical-critical literature review approach using sources from national and international journals published between 2023 and 2025, obtained through various scientific databases. The findings indicate that knowledge, attitudes, psychological factors such as self-compassion, the use of social media, as well as campus environmental support and health education programs play important roles in enhancing students’ awareness and healthy lifestyle behaviours. However, variations in the consistency of implementation are still observed. Conclusion of this study was improving awareness of a healthy lifestyle culture requires a comprehensive and sustainable approach through the integration of education, environmental support, and psychological factors. Higher education institutions are expected to develop structured health promotion programs and utilize digital technology to enhance the effectiveness of health education.